SISTEM INFORMASI INVENTARIS BARANG BERBASIS WEB PADA BALAI TEKNOLOGI AIR MINUM BEKASI - Firmansyah, Aldy; Purwanto, Heru; Putri, Eri Engelina (Journal of Information System, Informatics and Computing, 2025)
In the development of information technology today, information systems are needed in the management of goods inventory data. This thesis discusses the development of a web-based inventory information system at the Bekasi Drinking Water Technology Center. This agency previously used a manual process in recording and reporting goods, which often caused delays in information, recording errors, and difficulty in tracking data. Data was collected through direct observation, and interviews with staff. The system was developed using the Waterfall method which consists of the stages of analysis, design, implementation, and testing. The application was built with CodeIgniter 4 framework and MySQL database. The implementation results show that the system can help manage the inventory of goods in a more orderly and controlled manner. The recording and reporting process is faster, more accurate, and can be accessed at any time by the Super admin, admin and user. This system is also considered capable of reducing recording errors, speeding up data searches, and supporting operational efficiency at the Bekasi Drinking Water Technology Center